2013
DOI: 10.1002/ajh.23549
|View full text |Cite
|
Sign up to set email alerts
|

Decreased survival in normal karyotype AML with single‐nucleotide polymorphisms in genes encoding the AraC metabolizing enzymes cytidine deaminase and 5′‐nucleotidase

Abstract: De novo acute myeloid leukemia with normal karyotype (NK-AML) comprises a large group of patients with no common cytogenetic alterations and with a large variation in treatment response. Singlenucleotide polymorphisms (SNPs) in genes related to the metabolism of the nucleoside analogue AraC, the backbone in AML treatment, might affect drug sensitivity and treatment outcome. Therefore, SNPs may serve as prognostic biomarkers aiding clinicians in individualized treatment decisions, with the aim of improving pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
1
16
2
Order By: Relevance
“…Decreased Ara-C transport over the cell membrane into the cytoplasm [6,22] or inactivation of DCK [23,24] can both offset the cytotoxic function of Ara-C. Our previous study showed continuous exposure to Ara-C could induce drug resistance with decreased transcription level of DCK and SLC29A1 as well as elevated mRNA expression of CDA (data not shown). Genetic variations, particularly SNPs, have been identified in these genes involved in Ara-C transport and metabolism [25][26][27]. Both in vivo and in vitro studies demonstrated that the activities of these enzymes are correlated with polymorphic gene variations [28,29], and some of these SNPs are even highly correlated with treatment response and survival of AML patients with Ara-C based chemotherapy [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased Ara-C transport over the cell membrane into the cytoplasm [6,22] or inactivation of DCK [23,24] can both offset the cytotoxic function of Ara-C. Our previous study showed continuous exposure to Ara-C could induce drug resistance with decreased transcription level of DCK and SLC29A1 as well as elevated mRNA expression of CDA (data not shown). Genetic variations, particularly SNPs, have been identified in these genes involved in Ara-C transport and metabolism [25][26][27]. Both in vivo and in vitro studies demonstrated that the activities of these enzymes are correlated with polymorphic gene variations [28,29], and some of these SNPs are even highly correlated with treatment response and survival of AML patients with Ara-C based chemotherapy [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…RRM1 rs1042919 and rs1561876 were related to intracellular Ara-CTP concentration, CR rate, and OS [29]. CDA rs2072671 and rs532545 were related to OS in a FLT3-ITD mutation-positive normal karyotype AML patient, and NT5C2 rs10883841 was related to OS in a FLT3-ITD mutationnegative case [30]. In addition, the SLC29A1 rs3734703 AA/AC genotype in combination with TYMS rs2612100 was significantly associated with relapse-free survival and DCK rs469436 was associated with OS in AML patients [13].…”
Section: Discussionmentioning
confidence: 96%
“…A large interindividual variability in serum CDA activity has been reported . The determination of CDA gene polymorphisms has shown promising but discrepant results with regards to their correlation with serum CDA activity and clinical activity of nucleoside analogues . This discrepancy between serum enzyme activity and CDA gene polymorphisms suggests that other factors are likely to contribute to the large interindividual variability in serum CDA activity.…”
Section: Introductionmentioning
confidence: 99%